Análise de ações dinâmicas que influenciam no colapso progressivo em estruturas - Vasconcelos Junior, Jayro Cosme Guimarães (Universidade Federal Rural do Semi-Árido, 2018)
Due to the occurrence of several accidents involving structures that were submitted to dynamic actions and with this they arrived at partial or total progressive collapse, the need to carry out deeper studies on non-static structural behavior, that is, dynamic loads that are variable in time. The present work tries to show the types of dynamic actions and to do numerical analysis done through the Finite Element Method to verify the behavior over time of the diagrams of bending moment, shear stress, axial force and displacement of a structure subjected to dynamic actions that depending on its magnitude can lead to progressive collapse. The first part of the study is divided into two situations, the first situation being an analysis made by the application of a short-duration impact load generated by a vehicle with a speed of 36 km / h that collided with one of the elements that make up the structure and the second is with a speed of 60 km / h. The second part of the study is an analysis made with two types of explosive charges, ie the first observation was made with a load of 5 kg of TNT and the second with 60 kg of TNT. The responses are obtained by comparing each case and observing the behavior that the structure will have at the most critical time, that is, in time 0.2 seconds for vehicular impact and 0.4ms for explosive charges. For the case of vehicle impact, the values in the diagrams in the critical time were the highest having an increase of up to 123%. For the analysis with explosives, the critical time presented increases of up to 280%. With these maximum values are calculated areas of additional steel so that the structure does not have significant damages due to a dynamic action, however one must take into account the feasibility of this increase in the element. Finally, the work shows that these considerations involving dynamic actions must be taken into account even in the structural calculation and through these studies made with the use of computational tools, it becomes easier for the engineers of the area to elaborate a method that avoid or correct any structural damage that could lead to partial or total collapse of a building
Monografia
Keywords: Cargas de impacto; Ações excepcionais; Método dos elementos finitos; ENGENHARIAS::ENGENHARIA CIVIL